1996
DOI: 10.1055/s-2007-972854
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged L-Carnitine Administration on Delayed Muscle Pain and CK Release After Eccentric Effort

Abstract: Eccentric muscle effort is known to induce delayed muscle soreness (DOMS) and muscle damage which are not responsive to medical treatment with the most common analgesic agents. The aim of the study was to investigate the effects of oral L-carnitine supplementation on pain (VAS scale), tenderness (pain thresholds) and CK release induced by a 20-min eccentric effort of the quadriceps muscle. A single-blind study was carried out on 6 untrained subjects (mean age: 26 +/- 3.8 yrs; mean height: 173 +/- 4.6 cm; mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
0
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 3 publications
6
30
0
7
Order By: Relevance
“…The lack of a creatine kinase response to exercise during LCLT is indicative of less disruption to the sarcolemma. Similar to our findings, Giamberardino et al (7) demonstrated that the creatine kinase responses to a 20-min eccentric step test were attenuated in subjects that consumed 3 g carnitine/day for 3 wk before exercise.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of a creatine kinase response to exercise during LCLT is indicative of less disruption to the sarcolemma. Similar to our findings, Giamberardino et al (7) demonstrated that the creatine kinase responses to a 20-min eccentric step test were attenuated in subjects that consumed 3 g carnitine/day for 3 wk before exercise.…”
Section: Discussionsupporting
confidence: 92%
“…These studies demonstrated that supplemental carnitine is effective in attenuating tissue damage as directly assessed via magnetic resonance imaging, muscle soreness, and postexercise markers of metabolic stress following eccentric exercise training [102] or intense resistance exercise [103][104][105] thus leading to a quicker recovery (2 to 3 g/day of elemental carnitine being supplied by L-carnitine L-tartrate, LCLT). In particular Volek and colleagues [103] analyzed the effects of L-carnitine (2g/d for 3 wk before exercise and during 4d recovery) on markers of muscle damage in trained adult man following 5 sets of 15-20 repetitions of squats at 50% of 1-RM.…”
Section: Carnitinementioning
confidence: 99%
“…Furthermore ROS generated beyond physiological limits are found to reduce muscle force production by altering calcium ion sensitivity in muscle and thus contributing to muscle fatigue [107] [108,109]. Lcarnitine supplementation has been related to reduced postexercise CK [102,103] and myoglobin [103,105] concentrations suggesting that reduced oxidative stress may play a role in a quicker muscle recovery from strenuous exercise following supplementation. As a matter of fact early studies by Brass et al (1993) [110] demonstrated that L-carnitine delays hypoxiainduced fatigue in electrically stimulated rat skeletal muscle in vitro through its key stimulatory role in muscle bioenergetics and antioxidant activity.…”
Section: Carnitinementioning
confidence: 99%
“…С помощью приема 2 г карнитина ежедневно бе гу-ны-стайеры улучшали спортивные показатели на 6%, что достаточно было для превращения участни-ка соревнований в чемпиона. [6]. Работа А. Френ ке-ля о необходимости карнитина для роста экспе ри-ментальных животных (1952) имела многочислен ные продолжения, которые позволили провозгласить карнитин незаменимой аминокислотой если не для взрослых, то для маленьких детей, особенно находящихся на искусственном вскармливании.…”
unclassified